2012
DOI: 10.1371/journal.pone.0032732
|View full text |Cite|
|
Sign up to set email alerts
|

Prioritizing Risks and Uncertainties from Intentional Release of Selected Category A Pathogens

Abstract: This paper synthesizes available information on five Category A pathogens (Bacillus anthracis, Yersinia pestis, Francisella tularensis, Variola major and Lassa) to develop quantitative guidelines for how environmental pathogen concentrations may be related to human health risk in an indoor environment. An integrated model of environmental transport and human health exposure to biological pathogens is constructed which 1) includes the effects of environmental attenuation, 2) considers fomite contact exposure as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 54 publications
0
29
0
Order By: Relevance
“…Different model forms can lead to very different extrapolated estimates from the same set of data. This creates substantial uncertainty regarding the minimum dose required to cause infection in humans [20] and the dose-dependent time from exposure to appearance of illness (incubation period), key parameters required for sound risk assessment by public health and emergency preparedness authorities [12], [21].…”
Section: Introductionmentioning
confidence: 99%
“…Different model forms can lead to very different extrapolated estimates from the same set of data. This creates substantial uncertainty regarding the minimum dose required to cause infection in humans [20] and the dose-dependent time from exposure to appearance of illness (incubation period), key parameters required for sound risk assessment by public health and emergency preparedness authorities [12], [21].…”
Section: Introductionmentioning
confidence: 99%
“…2 QMRA also provides a mechanism for developing technically informed disinfection goals for surface hygiene and safety. 3,4 Fomites have been recognized as important in the spread of infectious disease, particularly through fomiteehand interactions and are common concerns in environments of high contacts (touches) with such pathogens as norovirus, influenza, and rotavirus, as well as and methicillin-resistant Staphylococcus aureus (MRSA). [5][6][7][8][9][10][11][12][13][14] Fomites have been associated with infectious disease outbreaks in such venues as cruise ships, restaurants and nursing homes, 15 schools, 16,17 daycare centers, 18 and gyms.…”
mentioning
confidence: 99%
“…Although the authors of this study are not aware of evidence that this is a practical concern for biosolids, existing literature studies do support the concept that non-detectable levels of pathogens might correspond to widely varying risk levels. Hong et al (2012) found that the detection limit for a pathogen can range from a risk on the order of 1 in 100 000 to a risk on the order of 1 in 10, depending on the pathogen. The expert who raised this concern explained that the issue could be addressed by establishing more rigorous and uniform sample size requirements for pathogen testing in Class A biosolids (see Hong et al, 2010 andHuang et al, 2010 for examples of how sampling requirements can be designed to meet risk targets), or by requiring specific treatment processes be used to achieve Class A status (i.e., eliminating the option of achieving Class A requirements based on testing alone).…”
Section: February 2013mentioning
confidence: 99%